The Challenges and Future of Immunotherapy for Gliomas. Issue 5 (September 2021) - Wu, Adela; Lim, Michael
Abstract: Gliomas and glioblastoma comprise the majority of brain malignancies and are difficult to treat despite standard of care and advances in immunotherapy. The challenges of controlling glioma growth and recurrence involve the uniquely immunosuppressive tumor microenvironment and systemic blunting of immune responses. In addition to highlighting key features of glioma and glioblastoma composition and immunogenicity, this review presents several future directions for immunotherapy, such as vaccines and synergistic combination treatment regimens, to better combat these tumors.